Exposure to hydroxyapatite nanoparticles enhances Toll-like receptor 4 signal transduction and overcomes endotoxin tolerance in vitro and in vivo. (November 2021) - Hua, Yuchen; Wu, Jinjie; Wu, Hongfeng; Su, Cheng; Li, Xiangfeng; Ao, Qiang; Zeng, Qin; Zhu, Xiangdong; Zhang, Xingdong
Abstract: Emerging studies indicate hydroxyapatite nanoparticles (HANPs) exhibit modest immunogenicity to elicit innate immune response which might involve Toll-like receptor 4 (TLR4) activation. This study was proposed to elucidate how HANPs direct over TLR4 signal activity in macrophage in response to TLR4 ligand, lipopolysaccharide (LPS). The present study for the first time reveals that HANPs themselves can induce TLR4 endocytosis and activate pathways both of nuclear factor-kappa B (NF-κB) and interferon regulatory factor 3 (IRF3), which potentially trigger the production of inflammatory cytokine by macrophage. Further, HANPs dose-dependently reprogram over LPS driven TLR4 signaling transduction in macrophage, leading to synergistically augmented innate immune response. In particular, HANPs synergize with LPS to promote macrophage polarization toward M1 phenotype. Moreover, HANPs abrogate the endotoxin tolerance in macrophages by restoring the production of inflammatory cytokines from macrophage in response to secondary LPS stimulation, and enhance the responsiveness of the body to LPS re-challenge in the endotoxin tolerance mice model. Therefore, this study sheds a new light on the mechanism by which HANPs drive the innate immune response, and offers a powerful strategy to potentiate LPS mediated TLR4 signaling activation in macrophage. Statement of significance: In recent years, increasing attention has been given to hydroxyapatite nanoparticles (HANPs) on how they interact with immune cells for achieving appropriate biological effect such as bone tissue repair, soft tissue filler, tumor treatment, vaccine delivery, et al. This study indicated HANPs can induce TLR4 signaling activation. In the further, HANPs dose-dependently synergize with LPS to program over LPS induced TLR4 signaling transduction in macrophage, to favor macrophage polarizing toward M1 phenotype, as well as to abrogate immune tolerance in macrophage in response to repeated LPS stimulation. This work opens a window for the intrinsic mechanism of HANPs to drive immune response and facilitate to direct the rational use or design of HANPs for their better biomedical application. Graphical abstract: Image, graphical abstract